Behavioral and physiological response of the passerine bird agelaioides badius to seeds coated with imidacloprid. - Poliserpi, Maria Belen; Abad, Tatiana Noya; De Geronimo, Eduardo; Aparicio, Virginia Carolina; Brodeur, Celine Marie (Springer, 2023)
Neonicotinoids are globally used insecticides, and there are increasing evidence on their negative efects on birds. This study is aimed at characterizing the behavioral and physiological efects of the neonicotinoid imidacloprid (IMI) in a songbird. Adults of Agelaioides badius were exposed for 7 days to non-treated peeled millet and to peeled millet treated with nominal concentrations of 75 (IMI1) and 450 (IMI2) mg IMI/kg seed. On days 2 and 6 of the trial, the behavior of each bird was evaluated for 9 min by measuring the time spent on the foor, the perch, or the feeder. Daily millet consumption, initial and fnal body weight, and physiological, hematological, genotoxic, and biochemical parameters at the end of exposure were also measured. Activity was greatest on the foor, followed by the perch and the feeder. On the second day, birds exposed to IMI1and IMI2 remained mostly on the perch and the feeder, respectively. On the sixth day, a transition occurred to sec tors of greater activity, consistent with the disappearance of the intoxication signs: birds from IMI1 and IMI2 increased their time on the foor and the perch, respectively. Control birds always remained most of the time on the foor. IMI2 birds signifcantly decreased their feed intake by 31% the frst 3 days, compared to the other groups, and signifcantly decreased their body weight at the end of the exposure. From the set of hematological, genotoxic, and biochemical parameters, treated birds exhibited an alteration of glutathione-S-transferase activity (GST) in breast muscle; the minimal efects observed are probably related to the IMI administration regime. These results highlight that the consumption of less than 10% of the bird daily diet as IMI-treated seeds trigger efects at multiple levels that can impair bird survival.